Determinants of uterine rupture in Dessie Referral Hospital, North East Ethiopia, 2016: case control design - Workie, Amare; Getachew, Yemmiamrew; Temesgen, Kibir; Kumar, Prem (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Uterine rupture remains a major obstetric problem particularly in less developed countries. The aim of this study was to identify determinants of uterine rupture among mothers getting delivery services in Dessie Referral Hospital from January 2016 to June 2016, North East Ethiopia. Methods: A prospective unmatched case control study was conducted recruiting 42 mothers with uterine rupture as case group and 168 for control group. Pretested, structured questionnaire was used to collect data. Results: Descriptive statistics and Logistic regression models were utilized considering 95% confidence interval and p-value of 0.05 to determine the presence and strength of association between dependent and independent variables. Majority (94.2%) of cases came from rural areas, 76.2% had obstructed labor and 55% had prolonged labor. Of 85.7% of cases have reported number of pregnancies ≥ 5. Mothers who encountered obstructed labor and previous Caesarean section scar were at higher risk of uterine rupture (AOR=22.2, 95% CI=2.8-4.1 and AOR=13.6, 95% CI=2.16-17.84 respectively). Mothers living in urban area, having Antenatal Care follow-up, shorter labor stay and primi-parity were found to have lower risk of uterine rupture. Conclusions: This study revealed that living in rural areas, absence of Antenatal Care follow-up, prolonged labor, obstructed labor, grand multiparity and previous Caesarean section scar were determinants of uterine rupture. Viable strategies have to be designed and implemented to tackle these determinants of uterine rupture.